2020
DOI: 10.21203/rs.3.rs-84443/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MiR-150-5p-modified Bone Marrow Mesenchymal Stem Cells Derived Exosomes Ameliorate Osteonecrosis of Femoral Head by Promoting Endothelial Cell Angiogenesis

Abstract: Background: Osteonecrosis of femoral head (ONFH) is a common ischemic disease that induces femoral head necrosis. The role of exosomes and miRNA in ONFH has been elucidated, however, whether miRNA-modified exosomes improve the therapy of ONFH is not clear.Methods: We screened ONFH-related miRNAs by RNA sequencing in plasma exosomes of ONFH patients and healthy donors. The key miRNA was overexpressed in bone marrow mesenchymal stem cells (BMSC) exosomes. The regulatory functions of miRNA-modified BMSC exosomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…For example, miR-150 secreted by monocytes has been shown to induce endothelial tube formation in vitro and angiogenesis in vivo , and down-regulation of miR-150 has been linked to an inhibition of angiogenesis seen in diabetes, cancer, and atherosclerosis. 58 Fang et al 59 elucidated the exosomal miRNA expression profile during osteonecrosis of femoral head (ONFH) and identified that miR-150-5p was significantly downregulated in exosomes within the plasma of the femoral head. Moreover, they demonstrated that miR-150-5p-modified MSC exosomes can promote angiogenesis potentially protecting against ONFH.…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-150 secreted by monocytes has been shown to induce endothelial tube formation in vitro and angiogenesis in vivo , and down-regulation of miR-150 has been linked to an inhibition of angiogenesis seen in diabetes, cancer, and atherosclerosis. 58 Fang et al 59 elucidated the exosomal miRNA expression profile during osteonecrosis of femoral head (ONFH) and identified that miR-150-5p was significantly downregulated in exosomes within the plasma of the femoral head. Moreover, they demonstrated that miR-150-5p-modified MSC exosomes can promote angiogenesis potentially protecting against ONFH.…”
Section: Discussionmentioning
confidence: 99%
“…Fang et al elucidated the exosomal miRNA expression profile during osteonecrosis of femoral head (ONFH) and identified that miR-150-5p was significantly downregulated in exosomes within the plasma of the femoral head. Moreover, they demonstrated that miR-150-5p-modified MSC exosomes can promote angiogenesis potentially protecting against ONFH [57]. The target genes of miR-150-5p participate in the TGFβ, MAPK, HIF-1, PI3K-Akt, and mTOR signalling pathways, all of which been linked to angiogenesis.…”
Section: Previous Work By Liu Et Al Has Shown That Fluid Shear Can Re...mentioning
confidence: 99%